2019
DOI: 10.3345/kjp.2018.07052
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for the occurrence and persistence of coronary aneurysms in Kawasaki disease

Abstract: Purpose Prognostic factors of coronary aneurysms in Kawasaki disease have been investigated in many studies. The aim of this study was to identify risk factors associated with early and late coronary artery outcomes in treated patients with Kawasaki disease. Methods A total of 392 patients diagnosed with Kawasaki disease from January 2012 to December 2015 in Pusan National University Children’s Hospital were retrospectively selected as subjects of the present study to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
(35 reference statements)
1
5
0
Order By: Relevance
“…Although reports on new therapeutic options for initial IVIG-resistant patients, such as steroid, infliximab, or repeated IVIG are available, their effectiveness in reducing the prevalence of coronary aneurysm remains controversial. Jeon et al [9] demonstrated that their findings of a predictive risk factor are comparable to that of Ha et al [6], and that Harada scores did not have a significant effect on coronary aneurysm [9]. Lin et al [10] suggested that the coronary severity 1 month after KD onset is most crucial to the late coronary outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although reports on new therapeutic options for initial IVIG-resistant patients, such as steroid, infliximab, or repeated IVIG are available, their effectiveness in reducing the prevalence of coronary aneurysm remains controversial. Jeon et al [9] demonstrated that their findings of a predictive risk factor are comparable to that of Ha et al [6], and that Harada scores did not have a significant effect on coronary aneurysm [9]. Lin et al [10] suggested that the coronary severity 1 month after KD onset is most crucial to the late coronary outcomes.…”
mentioning
confidence: 99%
“…In this issue of the Korean Journal of Pediatrics , Jeon et al [9] presented risk factors for the occurrence and persistence of coronary aneurysm in an interesting title in pediatrician’s, field of treatment that deals with KD. In this retrospective study, comprising 392 subjects, they reported the risk factors associated with early and late coronary artery outcomes in the patients treated for KD.…”
mentioning
confidence: 99%
“…In some patients, fever may persist for weeks, prolonged fever is usually associated with a higher incidence of cardiac involvement. Jeon et al (24) enrolled 392 KD patients, and they found that CAL group showed signi cantly longer duration of the febrile stage than non-CAL group (7.2 ± 2.4 vs 5.3 ± 1.4 days, P 0.05).…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, it is known that the platelet counts in KD patients are positively correlated with fever duration, and a longer inflammation period may be reflected in the increase in platelet counts (27). Jeon et al (28) observed that coronary artery aneurysms developed in 30 of 392 patients with KD within a month of diagnosis while in 20% they persisted even after 1 year of follow-up. High platelet counts and long-term fever are independent indicators of coronary artery aneurysm immediately after diagnosis.…”
Section: Assignment -------------------------------------------------mentioning
confidence: 99%